Is Social Media a Digital Pulpit? How Evangelical Leaders Use Twitter to Encourage the Faithful and Publicize Their Work. - Burge, R. P.
Social media is altering how some religious leaders communicate with their followers and with the public. This has the potential to challenge theories of religious communication that have been developed through the study of traditional modes such as sermons. This study examines how leaders in U.S. evangelicalism take advantage of the public platform provided by Twitter. Using over 85,000 tweets from 88 prominent evangelical leaders, we find that these leaders often use their social media platforms as a natural extension of their current modes of communication. More specifically, evangelical leaders use their account to encourage and inspire their followers, while also conveying information about upcoming personal projects such as tours and book releases. In a small number of cases, evangelical leaders do make reference to political issues, but those individuals are ones who have already built a brand based on political commentary. Speaking broadly, the usage of political language by evangelical leaders is rare. The paper concludes with a discussion of how this analysis advances theories of religion and communication.KeywordsTwitter ? social media ? evangelicals ? leaders
Keywords: Twitter; Social media; Evangelicals; Leaders